Historical and theoretical traditions of knowledge in management systems - Goncharenko M. V. Mark Vasilievich; Rogotneva E. N. Elena Nikolaevna; Demidova O. M. Olga Mikhailovna; Michalzhova E. (2016, 2016)
Title screen